Comparison of indirubin concentrations in indigo naturalis ointment for psoriasis treatment: a randomized, double‐blind, dosage‐controlled trial. (1st January 2018) - Lin, Y.‐K.; See, L.‐C.; Huang, Y.‐H.; Chi, C.‐C.; Hui, R.C.‐Y.
Summary: Background: Indigo naturalis and its refined formulation, Lindioil, are effective in treating psoriatic symptoms topically. Indirubin is the active ingredient in indigo naturalis. Objectives: To determine the efficacy and safety of different concentrations of indirubin in Lindioil ointment for treating psoriasis. Methods: In this randomized, double‐blind trial, adult patients presenting with chronic plaque psoriasis for > 1 year and with < 20% of the body surface area (BSA) affected were randomized to apply Lindioil ointment containing 200, 100, 50 or 10 μg g −1 of indirubin twice daily for 8 weeks followed by an additional 12‐week safety/extension period. The primary end point was the mean percentage change in Psoriasis Area and Severity Index (PASI) score along with the proportion of participants achieving 75% and 90% reductions in PASI scores (PASI 75 and PASI 90, respectively) from baseline to week 8. Results: The results from week 8 revealed that the 200 μg g −1 group had the greatest reduction in PASI score [69·2%, 95% confidence interval (CI) 55·5–82·8], followed by the 100 μg g −1 group (63·1%, 95% CI 52·8–73·5), the 10 μg g −1 group (53·4%, 95% CI 42·8–64·0) and the 50 μg g −1 group (50·3%, 95% CI 37·4–63·2), with a between‐group comparison of P = 0·0445. The group with the highest proportion of the patients achieving PASI 75 (57%, P = 0·0474) and PASI 90 (30%, P = 0·0098) was the 200 μg g −1 group. No severe treatment‐related adverse events were reported during the 20‐week evaluation. Conclusions: An amount of 200 μg g −1 of indirubin in Lindioil ointment is the most effective concentration studied so far for treating psoriasis topically, and is safe.